Multiple Visions, Multiple Voices: A Dialogic Methodology for Teaching in Higher Education. (July 2019) - Formenti, Laura; Jorio, Federica
This article aims at contributing to the development of teaching methodologies which can foster transformative learning in higher education. It presents a workshop experience, embedded in an undergraduate course, whereby active and dialogic methodology was designed to support the students in maturing self-awareness about their epistemologies and perspectives. The workshop used video narrative as language that allows exploration of the students' assumptions and the cross-media portfolio to support the learning process in its unfolding. In the first part of the article, we introduce the theoretical frame and contextual premises of the workshop and our different contributions to this study. Then we describe our methodology, through its multiple—visual, narrative, reflective, and reflexive—layers. Finally, we use dialogue to analyze a student's cross-media portfolio, as an in-depth example of the methodology employed. Our analysis illustrates the complexity and learning potential of this experience of transformative learning practices beyond self-report.